Hydraulic engineering of dams - Hager, Willi (Boca Raton, Florida : CRC Press, 2021)
Hydraulic engineering of dams and their appurtenant structures counts among the essential tasks to successfully design safe water-retaining reservoirs for hydroelectric power generation, flood retention, and irrigation and water supply demands. In view of climate change, especially dams and reservoirs, among other water infrastructure, will and have to play an even more important role than in the past as part of necessary mitigation and adaptation measures to satisfy vital needs in water supply, renewable energy and food worldwide as expressed in the Sustainable Development Goals of the United Nations.